Mobilizing satisfied users for promoting family planning final report on a pilot study in the eastern Visayas region of the Philippines - Soledad, Daisy R.; Barloso, Wilfred G.; Mateo, Domingo A.; Abilar, Antonio A.; Mondragon, Dominador B. (1997)
The project described here attempted to increase prevalence of use of more effective family planning methods (MEM) and of contraceptive practice in general in large, geographically dispersed barangay supply point (BSP) areas in Region 8 of the Philippines. Sixty volunteer motivators were selected and trained, using a modified version of the BSP officers' training curriculum with emphasis on motivational aspects. An experimental design with two experimental groups and a control group (randomly allocated) was employed.
The purposes of the project were to determine (1) the effectiveness and cost-effectiveness of utilizing trained volunteer motivators, (2) the procedural or implementation problems associated with motivational activities, and (3) the needs for enrichment of the training curriculum and improvement of selection criteria for volunteers in the family planning program. Three hypotheses were tested: 1. Overall and MEM prevalence rates will increase more in the experimental BSP areas than in the control areas. 2. Prevalence rates will increase more in the areas with two trained volunteer motivators than in those with only one. 3. The cost of increasing the prevalence rate of MEM users in the experimental areas will be less than that in the control areas.
Quantitative analysis for testing these hypotheses provides no support for the first two hypotheses in the study area as a whole. The first hypothesis received support in one geographic area (the subprovince of Biliran); however, the small number of sample BSPs in this area render the significance of this finding inconclusive. Since the findings showed no clear evidence of an increase in the MEM prevalence rates in the experimental areas relative to the change in the control areas, no test of the third hypothesis was attempted.
Qualitative analysis of data based on field observations and interviews with volunteer motivators and population field workers revealed extensive evidence that the failure of the intervention to increase MEM prevalence was due largely, if not entirely, to shortcomings in the selection, motivation, training, and supervision of the volunteer motivators. As a result, the present study does not provide an adequate test of the hypotheses.
A research study (Graduate Studies and Research Program) -- University of the Philippine, Tacloban.